Unexpected Vection Exacerbates Cybersickness During HMD-Based Virtual Reality - Teixeira, Joel; Miellet, Sebastien; Palmisano, Stephen (Frontiers in Virtual Reality, 2022)
Visually induced illusions of self-motion (vection) are thought to cause cybersickness during head-mounted display based virtual reality (HMD VR). However, the empirical support for this widespread belief is rather mixed. Our exploratory study examined the possibility that only unexpected experiences of vection provoke cybersickness. Fifteen males and 15 females played an HMD VR game (Mission: ISS) for up to 14 minutes with: 1) their experiences of vection and cybersickness assessed every two minutes; and 2) the game being terminated whenever they reported feeling sick. Of the 30 participants tested, 17 reported feeling sick and 13 remained well. Sick and well participants did not differ in terms of the strength of their vection experiences. However, the sick participants were significantly more likely to report unexpected/uncontrolled vection. When these data were subjected to machine learning analysis, unexpected vection was found to be the most important predictor of cybersickness. These preliminary findings suggest that vection can be used to safely enhance experiences in HMD VR – as long as developers ensure that any simulated self-motions are expected and perceived to be under the user’s control.